2010
DOI: 10.1177/1933719110377118
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation of Progesterone Receptor Isoform B (PR-B) in Adenomyosis and Its Rectification by a Histone Deacetylase Inhibitor and a Demethylation Agent

Abstract: Adenomyosis is a fairly common gynecologic disease with unknown pathogenesis. We sought to investigate as to whether the promoter of progesterone receptor isoform B (PR-B) is hypermethylated in adenomyosis and to investigate the treatment of ectopic endometrial stromal cells with trichostatin A (TSA), a histone deacetylase inhibitor (HDI), and 5-aza-2-deoxycytidine (ADC), a demethylation agent, on PR-B gene and protein expression, and on cell viability. Ectopic endometrial tissue specimens were obtained from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…These results also suggest that, in preclinical studies of potential therapeutic agents, these 3 measurements may serve as biomarkers gauging the potential efficacy. Indeed, PR-B is known to be involved in adenomyosis, 46,68 and as a transcription factor it may be a pivotal player. Myometrial OTR also seems to play a role in symptomatic adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggest that, in preclinical studies of potential therapeutic agents, these 3 measurements may serve as biomarkers gauging the potential efficacy. Indeed, PR-B is known to be involved in adenomyosis, 46,68 and as a transcription factor it may be a pivotal player. Myometrial OTR also seems to play a role in symptomatic adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that progesterone receptor isoform B (PR-B) is hypermethylated in adenomyosis, which leads to PR-B silencing and possibly accounts for progesterone resistance, and, as such, histone deacetylase inhibitors and demethylation agents may be useful in reactivating PR-B and suppressing proliferation of ectopic endometrial tissues. 16 In addition, we have recently shown aberrant immunoreactivity to DNA methyl transferase (DNMT)-1 and DNMT-3B and also to class I histone deacetylases (HDACs) in adenomyosis. 17,18 The EGCG has been shown to suppress DNMTs and decrease HDAC activity, resulting in the reactivation of methylation-silenced genes.…”
Section: Introductionmentioning
confidence: 99%
“…First, a pilot study has shown that the use of valproic acid (VPA), a histone deacetylase inhibitor (HDACI), resulted in the relief of dysmenorrhea and the reduction of uterus size in women with symptomatic adenomyosis [5]. Second, it has been shown that, as in endometriosis [6], the progesterone receptor isoform B is hypermethylated and can be reactivated by an HDACI and/or a demethylation agent [7]. Our very recent study on a 12-patient case series indicates that the 3-month oral administration of VPA completely resolves dysmenorrhea and reduces the amount of menses and uterus size [8].…”
Section: Introductionmentioning
confidence: 99%